USE OF SPICES AS IMMUNITY BOOSTER A PRELIMINARY SURVEY WITHIN THE GENERAL POPULATION - Kamble, Manali; Gajbhiye, Nilima (International Journal of Research -GRANTHAALAYAH, 2023)
Immunity is the body’s defence system to fight various pathogenic agents including bacteria, viruses, and other infectious agents. Healthy people with a healthy immune system can fight infections better than those who are immunocompromised. Studies have shown that diet plays a key role in improving the immune response. Also, the consumption of certain herbs and spices has been associated with health benefits. India is among the leading countries to consume significant amounts of spices. The consumption of spices in the form of a concoction increased further during the COVID-19 pandemic. This concoction is traditionally called Kadha. Over time, people have realized the benefits of Kadha not just in fighting infection but in overcoming various health conditions. The current study surveyed around 83 people from India to understand the use of Kadha within the general population in India as a source to boost immunity. It also aimed to understand their perspective on the most suitable spice. This preliminary survey highlights that among the surveyed population, the majority of the participants considered Kadha as an immune booster (75%) that helps in relieving colds and coughs (73%). The majority of participants selected turmeric (68%) and clove (66%) as spices that help to boost immunity and fight infections.